CERPEN “KOROSHIYA DESU NO YO” SEBUAH KAJIAN FEMINISME - Yuliani Rahmah (Izumi, 2016)
This article discusses about the Japanese short story which studied by feminism approach.. As the object of this study is one of Hoshi Shin Ichi‟s shortstory Koroshi desu no yo. This short story told about a female figure called Onna that with her intelligence, she can defeated the men of the upper classes. With the approach of power feminism, the authors conducted a study on the Onna‟s figure as main female character to find what kind a power that she used againts male domination in Japanese society and how she used that to reach her goal. As a result it is known the forms of feminine power which is owned by prominent Onna, and what kind of achievement that Onna can get by using girl power she has. As a woman this Onna figures as main character were able to show that power she had can make her survive in a society dominated by men. She also was able to show her existence as an independent individual and get the same rights as men.